Surface characterization and grinding of Duplex 2205 Stainless Steel slabs - Ahmad, Ari (My University, 2025)
This study investigates the optimization of grinding processes for duplex 2205 stainless steel slabs at Outokumpu Avesta works. The primary objective is to analyze and enhance these processes to achieve cost reductions, increased productivity, and improved material processing efficiency. To fulfill this aim, a combination of theoretical analysis and practical experiments has been conducted, with a particular focus on the effects of different grinding methods on oxidation levels and surface quality. Through the evaluation of various grinding conditions, the study identifies opportunities for process improvements that can enhance production efficiency. It is shown that implementing coarse grindings process only can reduce total material loss by 21 ton, decrease grinding time by 200 hours, and result in potential savings of 40% in grinding wheel costs during the reference period. The findings highlight the need to balance cost-effectiveness, product quality, and environmental considerations. This work aims to support Outokumpu's long-term development strategy while contributing to the company's competitiveness in the global market